An evidence-based treatment algorithm for colorectal polyp cancers: results from the Scottish Screen-detected Polyp Cancer Study (SSPoCS). Issue 2 (27th October 2016) - Richards, CH; Ventham, NT; Mansouri, D; Wilson, M; Ramsay, G; Mackay, CD; Parnaby, CN; Smith, D; On, J; Speake, D; McFarlane, G; Neo, YN; et al.
Abstract : Objectives: Colorectal polyp cancers present clinicians with a treatment dilemma. Decisions regarding whether to offer segmental resection or endoscopic surveillance are often taken without reference to good quality evidence. The aim of this study was to develop a treatment algorithm for patients with screen-detected polyp cancers. Design: This national cohort study included all patients with a polyp cancer identified through the Scottish Bowel Screening Programme between 2000 and 2012. Multivariate regression analysis was used to assess the impact of clinical, endoscopic and pathological variables on the rate of adverse events (residual tumour in patients undergoing segmental resection or cancer-related death or disease recurrence in any patient). These data were used to develop a clinically relevant treatment algorithm. Results: 485 patients with polyp cancers were included. 186/485 (38%) underwent segmental resection and residual tumour was identified in 41/186 (22%). The only factor associated with an increased risk of residual tumour in the bowel wall was incomplete excision of the original polyp (OR 5.61, p=0.001), while only lymphovascular invasion was associated with an increased risk of lymph node metastases (OR 5.95, p=0.002). When patients undergoing segmental resection or endoscopic surveillance were considered together, the risk of adverse events was significantly higher in patients with incomplete excision (OR 10.23, p<0.001) or lymphovascular invasion (OR 2.65, p=0.023). Conclusion: A policy of surveillance is adequate for the majority of patients with screen-detected colorectal polyp cancers. Consideration of segmental resection should be reserved for those with incomplete excision or evidence of lymphovascular invasion.